2016
DOI: 10.1523/jneurosci.1079-16.2016
|View full text |Cite
|
Sign up to set email alerts
|

Mutant α-Synuclein Overexpression Induces Stressless Pacemaking in Vagal Motoneurons at Risk in Parkinson's Disease

Abstract: Overexpression of mutant α-synuclein causes Parkinson's disease, presumably by driving neurodegeneration in vulnerable neuronal target populations. However, the extent of α-synuclein pathology (e.g., Lewy bodies) is not directly related to the degree of neurodegeneration across various vulnerable neuronal populations. Here, we show that, in contrast to dopamine neurons in the substantia nigra, vagal motoneurons do not enhance their excitability and oxidative load in response to chronic mutant α-synuclein overe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

6
16
0
3

Year Published

2016
2016
2022
2022

Publication Types

Select...
3
3
1

Relationship

2
5

Authors

Journals

citations
Cited by 27 publications
(25 citation statements)
references
References 60 publications
6
16
0
3
Order By: Relevance
“…To address this, we measured voltage activated Ca 2+ (Cav) currents. We found that the total Cav currents in DMV neurons were reduced (data not shown), as shown previously in transgenic mice overexpressing human A53T a-synuclein (Lasser-Katz et al, 2017). Intriguingly, the reduction in Cav currents of DMV neurons in the AAV-A53T-transfected mice matched the reduction in their surface area.…”
Section: Figure 2 Gastrointestinal Motility Is Slowed In the Mouse Msupporting
confidence: 90%
See 3 more Smart Citations
“…To address this, we measured voltage activated Ca 2+ (Cav) currents. We found that the total Cav currents in DMV neurons were reduced (data not shown), as shown previously in transgenic mice overexpressing human A53T a-synuclein (Lasser-Katz et al, 2017). Intriguingly, the reduction in Cav currents of DMV neurons in the AAV-A53T-transfected mice matched the reduction in their surface area.…”
Section: Figure 2 Gastrointestinal Motility Is Slowed In the Mouse Msupporting
confidence: 90%
“…We have shown previously that DMV neurons in transgenic mice that globally overexpresses human A53T a-synuclein undergo cell-autonomous adaptations (compared with control mice) in the form of a transcriptional downregulation of Cav currents, which leads to lower basal mitochondrial oxidative stress (Lasser-Katz et al, 2017). In the current, adult onset brain stem-selective a-synucleinopathy model, we replicated the reduction in total Cav current.…”
Section: Discussionsupporting
confidence: 70%
See 2 more Smart Citations
“…Boxplots represent range (whiskers), median (thick bar) and lower and upper quartiles. In the current-voltage and current-LED intensity curves the medians of each measurement are presented with confidence intervals given by the 50% × (1 ± 1/√ n ) percentiles, where n is the sample size (Lasser-Katz et al, in press). The parametric ANCOVA test was used to test significant changes in these curves.…”
Section: Methodsmentioning
confidence: 99%